Deep equality in an era of religious diversity - Beaman, Lori G. (Oxford University Press, 2017)
While religious conflict receives plenty of attention, the everyday negotiation of religious diversity does not. Questions of how to accommodate religious minorities and of the limits of tolerance resonate in a variety of contexts and have become central preoccupations for many Western democracies. What might we see if we turned our attention to the positive narratives and success stories of the everyday working out of religious difference? Rather than 'tolerance' and 'accommodation', and through the stories of ordinary people, this book traces deep equality, which is found in the respect, humour, and friendship of seemingly mundane interactions. Deep Equality in an Era of Religious Diversity shows that the telling of such stories can create an alternative narrative to that of diversity as a problem to be solved. It explores the non-event, or micro-processes of interaction that constitute the foundation for deep equality and the conditions under which deep equality emerges, exists, and sometimes flourishes